Functional health literacy among chronic cardiac patients: scoping review (Revista Contexto & Saúde, 2025)
Objective: To map functional health literacy strategies developed with chronic cardiac patients under outpatient follow-up. Method: This is a scoping review study, based on the Joanna Briggs Institute Reviewer’s Manual, with searches conducted in the following databases and portals: LILACS, Embase, Cochrane, MEDLINE/PubMed, Web of Science, ScienceDirect, Scopus, SciELO, and gray literature (BDTD). The initial sample comprised 2,199 studies, of which 327 were removed as duplicates. At the end of the selection process, 287 articles were analyzed in full, and only 16 answered the research question. Results: Findings indicate that health literacy contributed to the adoption of more positive behaviors, such as improved self-care. However, the study also revealed that patients under follow-up still presented difficulties in understanding their health condition—especially older adults. Conclusion: The results point to a promising scenario; however, current efforts remain insufficient to affirm definitive changes in knowledge and behaviors.
Keywords: Health literacy; Health education; Cardiovascular disease; Heart disease